Balaghah dalam Al-Qur’an: Analisis Al-Mubalaghah dalam Surah Al Hasyr Ayat 1-2 - Aslam Annashir; Mita Atiiqah Br Ginting; Harun Ar-Rasyid (Reflection : Islamic Education Journal, 2025)
Al Quran is an Arabic book that has beautiful sentences. To understand the meaning of this sentence, various knowledge of Arabic is needed. Among them is al mubalaghah. Al mubalaghah is a branch of the science of balaghah which studies understanding the meaning of Arabic. This research aims to deepen understanding of the verses of the Koran which contain mubalaghah. The research method used is literature study with a qualitative approach. The findings show that there are many mubalaghah in Surah Al Hasyr.